Foxp3 Gene Expression Value in Regulatory T Cells in Pathogenesis of Graft-Versus-Host Disease Induced with Cryopreserved Allogenic Material - Goltsev, Anatoliy N.; Dubrava, Tatuyana G.; Gayevskaya, Yuliya A.; Lutsenko, Elena D.; Ostankov, Maxim V.; Matsevitaya, Irina Yu. (Problems of Cryobiology and Cryomedicine, 2014)
Content of regulatory T cells (Treg) and their Foxp3 gene expression level in the recipients with graft-versus-host disease (GVHD) induced by introduction of fresh aspirated or cryopreserved allogenic bone marrow combined with lymph node cells were under study in this research. In GVHD experimental model the deficiency in Tregwas shown to play an important role in maintaining autoimmune process. In the animals with GVHD induced with fresh aspirated allogenic bone marrow (BM) almost twofold decrease in both Tregcontent and the expression level of Foxp3 gene were established as compared to the syngeneic BM recipients. An increased level of Foxp3 gene expression under the maximum reduction of their content in the animals with GVHD, induced with cryopreserved allogenic BM introduction, was noted. Cryopreservation of allogenic BM, used for GVHD induction, reduced its immune reactivity and, as a result, clinical evidence of pathology. Our findings enable to broaden the notion about the mechanisms of immune conflicts development in GVHD both at cellular and molecular levels. Probl Cryobiol Cryomed 2014; 24(4):322-331.